Multichannel electron transmission and multiple light scattering in CoCo PBA/CoSn(OH)6/Pt photocatalyst for effective conversion of simulated flue gas. (15th February 2023) - Wu, Wenting; Wu, Yuanfeng; Zhang, Zongqi; Sun, Lipeng; Wei, Ruiping; Zhang, Jin; Gao, Lijing; Pan, Xiaomei; Yu, Jin; Xiao, Guomin
Graphical abstract: Highlights: A CoCo PBA/CoSn(OH)6 /Pt heterojunction with unique inlaid structure is constructed. Visible-light-driven high selectivity conversion of simulated flue gas is achieved. Multichannel electron transmission promotes the separation and migration of photocarriers. A structure-modulated photocatalytic reaction mechanism is proposed. Abstract: Converting industrial waste gas into high-value chemicals is crucial to sustainable economic development. Herein, through a coordination strategy of facet-selective etching and in-situ growth, the CoCo Prussian blue analogue (PBA)/CoSn(OH)6 /Pt heterojunction was designed and prepared with multiple interfaces and dual interconnection networks, which is suitable for photocatalytic conversion of simulated flue gas. This unique structure is conducive to multi-channel electron transmission and multiple light scattering, promoting the separation and migration of photogenerated carriers. This photocatalyst can synergistically regulate charge potential and kinetics, and enhance CO2 activation. Therefore, the CO generation rate (11.7 µmol·g −1 ·h −1 ) and selectivity (91.8 %) of the CoCo PBA/CoSn(OH)6 /Pt heterojunction were significantly improved without using additional photosensitizer or sacrificial agent. The mechanism and reaction pathway of photocatalytic CO2 reduction were further studied by in-situ technology and density functional theory (DFT) calculation. This study offers knowledge about the preparation of high-efficiency photocatalysts for flue gas conversion and structure-modulated photocatalytic reaction.